Medium land rice production in Puri district of Odisha: an economic analysis - Haqjo, H R; Prusty, Suvashree R; Mishra, R K; Dixit, B K (ORYZA-An International Journal of Rice, 2018)
Rice is a staple food in Odisha as it is grown on an area of 4.4 million hectares. In the context of higher demand for rice, any strategy that would produce higher yield with less cost is the need of the day. The general objective of the study is to find the economics of production of rice emphasizing on benefit cost ratio. A study was conducted in Puri district of Odisha to find out the cost, return, farm and resource use efficiency of rice in the year 2015-16. A multi-stage random sampling method was used to draw the sample. Primary data was collected from 60 respondents, consisting of 20 marginal, 20 small and 20 large farmers. It was found that, the total cost on an average Rs. 14041.15 in all farms out of which total variable cost Rs. 11048.9 of which marginal farmer, small farmer and large farmer expended Rs. 9940.50, Rs. 10029.91 and Rs. 13175.99 respectively that was 78.60% of total cost. Total fixed cost was Rs. 2992.25 out of which marginal farmers, small farmers and large farmers expended Rs. 2613.10, Rs. 3088.67 and Rs. 3275.00 respectively which was 21.32% of total costs. Yield of rice was highest in case of large farms i.e. 20.58 q/ha followed by small farms 16.45 q/ha and marginal farms 14.00 q/ha. On an average, the total revenue was Rs. 42842.67 for all farms out of which marginal, small and medium farmers got the net return of Rs. 41354.00, Rs. 27132.40 and Rs. 60041.60 respectively. Benefit cost ratio was 2.27 for all farms. Labour, machine, fertilizer and pesticide are under utilization where as manure is over utilized in the study area. Insufficient capital is important production problem in the study area. Suitable funding agency is also a lacuna in the area. Government should provide more subside to the marginal and small farmer as it is given upto 25% of the cost of plants and machineries in case of rice.